Transformasi Pesantren Sebagai Hubungan Ekonomi: Strategi Pemberdayaan Umkm dan Dampaknya Terhadap Ketahanan Lokal - Bella Findayani; M. F. Hidayatullah (PT Maju Malaqbi Makkarana, 2026)
This study aims to examine the transformational role of Islamic boarding schools (pesantren) as centers of economic activity in empowering micro, small, and medium enterprises (MSMEs) managed by students and alumni, and its implications for strengthening local economic resilience. As their roles evolve, Islamic boarding schools (pesantren) no longer function solely as religious educational institutions but also as strategic actors in community-based economic development that can drive improvements in community welfare. This study used a qualitative approach with a case study method in several Islamic boarding schools (pesantren) that have developed economic empowerment programs. Data were collected through in-depth interviews, field observations, and documentation analysis to gain a comprehensive understanding of the transformation patterns and their impact on business actors. The results indicate that the empowerment strategies implemented include increasing entrepreneurial capacity through training and coaching, ongoing business mentoring, facilitating access to capital sources, and strengthening marketing networks. The implementation of these strategies has been proven to contribute to increasing the capacity and performance of MSMEs, expanding employment opportunities, and strengthening local economic resilience through increasing community economic independence. These findings confirm that Islamic boarding schools have a strategic position as centers for community economic empowerment and have the potential to become models for inclusive, participatory, and sustainable economic development.